Total Nitrogen Absorption in Soil and its Uptake by Amaranthus cruentus Plant in Kwadon, Yamaltu/Deba Local Government Area of Gombe State, Northeastern Nigeria - B. Hammani; A. F. Tijjani; I. Abubakar; O. O. Akinlotan; A. Danladi (Journal of Applied Sciences and Environmental Management)
The objective of this paper was to investigate the total nitrogen absorption in soil and its uptake by Amaranthus cruentus plant in Kwadon, Yamaltu/Deba Local Government Area of Gombe State, Northeastern Nigeria using appropriate standard procedures. Data obtained show that the total N content was 0.53-1.32% with manure at 0-15 and 0.28-0.87% with manure at 15-30, while total N was obtained to be 0.19-0.53% without manure (control) at 0-15 and 0.11-0.59% at 15-30 without manure (control). The Amaranthus cruentus total N content was 0.06-2.10% with manure at 0-15 and 0.06-0.15% with manure at 15-30, whereas total N was obtained to be 0.02-0.09% both at 0-15 and 15-30 without manure (control). The total N content in soil was relatively higher than that of Amaranthus cruentus. The crop growth rate (GGR) was highest (146.21) and lowest (92.73) and (128.39) and lowest (61.54) on manure at days 0-15 and 15-30 of application, respectively. A similar trend was observed for total dry matter production (TDMP), leaf area index (LAI), leaf area ratio (LAR), and net assimilation rate (NAR). The highest (53.72) and lowest (25.42), and (53.72) and lowest (25.42) TDMPs were recorded on 15-30 and 0-15, respectively. The LAR and NAR were also the highest (5.31 and 0.07, respectively) on manure at day 0-15 after application. The lowest (2.21) LAR and (0.04) NAR were observed on days 0-15 after the application of manure. The manure exhibited the smallest positive changes in LAI, CGR, LAR, NAR, and TDMP after 15-30 days of application.